a) x khác 1
b)
/ (căn x) + 2 (căn x) - 2 \ (căn x)
| ------------------------- - ---------------------- | : ---------------------- <=>
\ x + 2(căn x) + 1 x - 1 / (căn x) + 1
/ (căn x) + 2 (căn x) - 2 \ (căn x) + 1
| ------------------------- - ---------------------- | x ---------------------- <=>
\ [(căn x) + 1]^2 x - 1 / (căn x)
x + (căn x) + 2(căn x) + 2 x + (căn x) - 2(căn x) - 2
--------------------------------------- - --------------------------------------- <=>
(x + căn x)^2 x(căn x) - (căn x)
(căn x)(căn x + 1) + 2(căn x + 1) (căn x)(căn x + 1) - 2(căn x + 1)
----------------------------------------------- - -------------------------------------------------- <=>
[(căn x)(căn x + 1)]^2 (căn x)(x-1)
(căn x + 2)(căn x + 1) (căn x - 2)(căn x + 1)
----------------------------------------------- - -------------------------------------------------- <=>
[(căn x)(căn x + 1)]^2 (căn x)(căn x +1)(căn x - 1)
(căn x + 2) (căn x - 2)
----------------------------------------------- - -------------------------------------------------- <=>
(căn x)^2 . (căn x + 1) (căn x)(căn x - 1)
(căn x + 2) (căn x - 2)
----------------------------------------------- - -------------------------------------------------- <=>
x(căn x) + x x - (căn x)
Còn lại bạn tự làm nhé